Anti-EGFR aptamer exhibits direct anti-cancer effects in NSCLC cells harboring EGFR L858R mutations - Brian J. Thomas; Sania Z. Awan; Trupti Joshi; Mark A. Daniels; David Porciani; Donald H. Burke (npj Precision Oncology)
Abstract Non-small cell lung cancer (NSCLC) adenocarcinoma (LUAD) is a leading cause of death worldwide. Activating mutations in the tyrosine kinase domain of the oncogene epidermal growth factor receptor (EGFR) are responsible for ~10–50% of all LUAD cases. Although tyrosine kinase inhibitors (TKIs) have been effective in prolonging patient survival and quality of life, acquired resistance and disease progression are inevitable, presenting a clear unmet need for alternative or adjuvant therapeutics. Here we show that an anti-EGFR aptamer (EGFRapt) decreases viability and tumor growth of LUAD cell lines harboring the L858R ± T790M mutation in EGFR. Additionally, we elucidate the mechanism by which EGFRapt exerts these effects by monitoring cellular processes associated with kinase-dependent and kinase-independent mechanisms. Overall, these data establish that EGFRapt has direct anti-cancer activity in mutant EGFR positive LUAD via targetable mechanisms that are independent of existing approaches, and they provide a foundation for further development of nucleic acid-based therapies that target EGFR.